Review on Security Based Vehicular Ad-Hoc Network - ., Sonika; Kumar Arora, Sandeep; Masud, Mahedi (International Journal of Engineering and Technology, 2018)
VANET a vehicular ad-hoc network provides the security to vehicles. To provide security in VANET, we are using Elliptical curve cryptography. In this paper we are going to discuss various techniques of cryptography, the techniques such are Advanced Encryption Standard, Data Encryption Standard, and Triple Data Encryption Standard. These techniques are part of symmetric and asymmetric cryptography. In addition to this there are some attacks which we are discussing in this paper like, masquerade attack, replay attack, insider attack, mutual authentication attack, and parallel session attack. These attacks are on different layer. At the end we are comparing these attacks with each other and compare their quality of services.Â